ҚАРАҚАЛПАҚ ТИЛИНДЕ ӨЛИМ МЕНЕН БАЙЛАНЫСЛЫ ЭВФЕМИЗМЛЕР - Матжанова, А.Ж. (SCIENCE and SOCIETY, 2024)
In the article, one of the important issues of linguistics is the search for euphemisms related to death. The main goal of the article is to identify euphemisms related to death used in the Karakalpak language.